Cigarette use among male and female grade 8–10 students of different ethnicity in South African schools. Issue 1 (1st March 2003) - Swart, D; Reddy, P; Ruiter, R A C; de Vries, H
Abstract : Objectives: To provide data on the prevalence of cigarette use by male and female South African students of different ethnic backgrounds in grades 8–10 (ages ⩽ 11 to ⩾ 17 years), their age of initiation of cigarette use, as well as their access to cigarettes through underage sales. Design: A nationally representative survey was conducted using self administered questionnaires translated into seven languages. Setting: School based. Participants: Students in grades 8–10 in all of South Africa's nine provinces. Outcome measures: The prevalence data for current users of cigarettes (smoked on one or more days in 30 days preceding the survey), and for the age of initiation (first smoking cigarettes before the age of 10) were analysed. Results: Of the 160 selected schools, 123 schools participated in the survey. The completed survey comprised 6045 of 7074 selected students; 23% of the sample reported being current users of cigarettes. Significantly more males (28.8%) than females (17.5%), and significantly more "Coloured" students than "Black/African" students were classified as current smokers. Sex was the strongest contributor to the prediction of current smoking status. On the issue of age of initiation, 18.5% of students reported having first smoked cigarettes before the age of 10 years with more "Black/African" students than "Coloured" having done so. Conclusions: In order to tailor tobacco control programmes to the needs of students, historical "racial"/ethnic and sex differences have to be taken into account. Specific determinant studies are needed to understand these differences and to develop appropriate responses.